Surgical treatment of complications of reconstructive operations in women–patients with tubular breasts of Type ІІ - A. A. Kostenko (Клінічна хірургія)
Objective. To analyze complications of reconstructive operations in women-patients with tubular breasts of Type ІІ, to propose the procedures of the complications correction and to estimate their results.